Calculating risks? : the spatial and political dimensions of hazardous waste policy - Hamilton, James, 1961- (Regulation of economic activity ;, 1999)
Annotation Hazardous wastes often head the public's list of environmental concerns. Exaggerated estimates of cancer epidemics arising from waste sites generate a sense of alarm, but little is known about the real extent of the health threats. In this book James T. Hamilton and W. Kip Viscusi present the first comprehensive analysis of the magnitude of hazardous waste risks and of the efficacy of the Environmental Protection Agency's Superfund program. By matching agency decision data to detailed census information using geographic information systems (GIS) technology, the authors show that most hazardous waste sites do not pose sufficient risk to merit the most stringent cleanup options. Those sites that do pose considerable risk to exposed populations often receive inadequate attention, because government decisions to target cleanups are based more on political factors than on actual risks. The authors propose policy reforms that could significantly reduce cleanup costs without sacrificing the protection of human health. Beyond its analysis of a particular risk policy, the book serves as a general model for comprehensive risk analysis.